2002
DOI: 10.1103/physrevc.66.051305
|View full text |Cite
|
Sign up to set email alerts
|

New0+states in158Gd

Abstract: A new high-precision (p,t) study of the 158 Gd nucleus was carried out with the Q3D spectrometer at the University of Munich. The result is the observation for the first time of a deformed nucleus with 13 excited 0 ϩ states below an excitation energy of approximately 3.1 MeV. Seven of these 0 ϩ states are observed for the first time and an additional three are new confirmations of previous tentative assignments. This abundance of 0 ϩ states provides significant new information on these poorly understood excita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
67
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 25 publications
5
67
3
Order By: Relevance
“…2 as filled triangles) in the order of excitation energies. The experimental data [9] are shown in the same plot for comparison. The predicted 0 + states are found to be in the right energy range, although deviations can be clearly seen between theory and experiment.…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…2 as filled triangles) in the order of excitation energies. The experimental data [9] are shown in the same plot for comparison. The predicted 0 + states are found to be in the right energy range, although deviations can be clearly seen between theory and experiment.…”
mentioning
confidence: 96%
“…Therefore, the calculation emphasized the quasiparticle character of these states, in contrast to previous work [10] using collective models. Our results were compared with the remarkable example of recently observed 13 excited 0 + states in 158 Gd [9]. After performing exact angular momentum projection and configuration mixing calculations (by two-body residual interactions) for all the possible low-lying qp configurations that can give rise to K π = 0 + states, we found that the obtained energy lev-…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The (p, t) pickup transfer reaction has been studied in an extensive campaign in the rare earth region [4][5][6][7][8][9] from Gd to Hg. This research has allowed a better understanding of the changes the nuclei undergo from the transitional Gd region -over the well-deformed Yb region -to the γ-soft Pt region and further towards the 208 Pb proton-neutron shell closure.…”
Section: Introductionmentioning
confidence: 99%